Preparation method of LOW DOI AG glass
Through two frosting and chemical polishing processes, LOW DOI AG glass with excellent optical performance was prepared, which solved the problem of insufficient eye comfort and visual clarity in the on-board display environment of existing AG glass, and achieved the balance of flash point, anti-glare effect and clarity.
Patent Information
- Application Number
- CN202411684925.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-11-22
AI Technical Summary
The existing AG glass products have insufficient eye comfort and visual clarity for eyes in vehicle display environments, and the single optical performance is not studied enough, so they cannot take into account the characteristics of flash point, anti-glare effect and clarity.
Two-time frosting + chemical polishing process were used to form a grain structure of relatively large and smaller particles through different frosting liquid formulations. Combined with chemical polishing treatment, LOW DOI AG glass with a flash point value of 4 < sparkle < 6, a clearness value of 65 < DOI < 80, a haze value of 15 < Haza < 25, and a gloss of 20 < G60 < 40 was prepared.
It provides good eye comfort and visual clarity in the on-board display environment, reduces the reflected interference of external light, and is suitable for on-board display applications.
Smart Images

Figure CN119591324A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of anti-glare glass, and in particular relates to a method for preparing LOW DOI AG glass. Background Art
[0002] AG (Anti-glare) glass, also known as anti-glare glass, is a glass with a special surface treatment. The specific principle is to process high-quality glass on one or both sides to make it have a lower reflectivity than ordinary glass, thereby reducing the interference of ambient light, improving the clarity of the picture, reducing screen reflection, making the image clearer and more realistic, and allowing viewers to enjoy better visual effects. AG glass can not only beautify the appearance and structure of decorations, but is also widely used in TV splicing walls, TVs, LCD monitors, touch screens and industrial instruments.
[0003] The production methods of AG glass generally include spraying, yellow light etching, and chemical etching. The first two methods are less used in the automotive display industry because they are greatly affected by the outside world and have poor reliability. The chemical etching method is easy to operate and produces products with high reliability, so it has become the mainstream of automotive AG glass production. As the automotive display industry has higher and higher requirements for safety and visual senses, it has put forward high requirements for anti-glare performance, display flare, eye comfort, etc., requiring the glass to be more comfortable to the eyes under the same vehicle lighting environment. This requires evaluating the comprehensive characteristics of each optical indicator of AG glass to obtain a set of optical properties that make it more user-friendly when displayed in a vehicle environment.
[0004] Chinese patent CN104609736B discloses an anti-glare liquid for glass and a preparation method thereof, and a method for preparing anti-glare glass using the anti-glare liquid. The liquid is prepared by mixing the following raw materials by mass fraction: 22% ammonium fluoride, 4.1% ammonium sulfate, 1.9% potassium sulfate, 2.8% calcium fluoride, 1.0% zinc chloride, 1.5% sodium fluorosilicate, 4.4% barium sulfate, 1.5% corn starch, 0.8% glucose solution with a mass concentration of 50%, 17% concentrated sulfuric acid with a mass concentration of 98%, and 43% deionized water. The anti-glare glass prepared has good light transmittance, uniform thickness, and is not easy to leave scratches and fingerprints on the surface. At the same time, there is no waste liquid and waste gas emission in the process of preparing the anti-glare glass, which is less harmful to operators and the environment and has good economic and social benefits.
[0005] Chinese patent CN102627407B discloses a process for treating the entire surface of glass with anti-glare and partial non-anti-glare, which mainly utilizes physical mechanical grinding, chemical etching and sandblasting to produce a fine concave-convex surface on the surface of electronic-grade glass. After being treated by this process, for touch panel products, the contact area can be reduced when the hand touches, and the resistance generated when the hand touches can be reduced, which is more flexible and easy to use. The anti-glare (AG) effect is directly made on the outer surface glass of the display. When looking at the screen, the external light is diffusely reflected, so that the eyes cannot feel the reflected light, so that the user can see the true color of the display well.
[0006] At present, the AG products on the market do not pay enough attention to the user experience of in-vehicle display. The focus is only on the single optical performance of the product, and the research on comprehensive performance is not deep enough. It is not suitable for the comfort of human eyes in the car environment. Specifically, the higher the clarity and glossiness of the glass and the smaller the haze, the greater the reflectivity of external light. In strong external light, the naked eye cannot see the screen clearly. On the contrary, the lower the clarity and glossiness of the glass and the greater the haze, the lower the reflectivity of external light. The naked eye can easily see the screen, but the transmitted light in the screen will be reduced, which will affect the clarity of the screen display. Therefore, it is necessary to select the appropriate comprehensive performance of glossiness, clarity and haze parameters, and analyze its crystal layer parameters to obtain LOW DOI AG glass that can take into account the characteristics of flash point, anti-glare effect, clarity, etc.
[0007] Summary of the invention: In view of the above technical problems, the present invention provides a method for preparing LOW DOI AG glass. Through two frosting + chemical polishing processes, a flash point value of 4<sparkle<6, a clarity value of 65<DOI<80, a haze value of 15<Haza<25, and a glossiness of 20<G 60 <40 LOW DOI AG glass with comprehensive properties, suitable for vehicle-mounted displays.
[0008] In order to achieve the above object, the present invention provides a method for preparing LOW DOI AG glass, comprising the following steps: (1) Screen print acid-resistant ink on one side of the glass and cure it, and passivate the other side; (2) frosting the glass obtained in step (1), and then washing with acid and water to obtain primary glass; (3) frosting the primary glass for a second time, then washing and air-drying to obtain secondary glass; (4) The secondary glass is chemically polished, and the acid-resistant ink is removed after cleaning and drying, and the low DOIAG glass is obtained by drying.
[0009] Preferably, the pickling in step (1) uses a hydrofluoric acid solution with a mass percentage of 0.5-1%.
[0010] Preferably, the time of the first frosting in step (2) is 60-120 seconds, and the temperature is 18-28° C.; the pickling adopts a hydrofluoric acid solution with a mass fraction of 1-2%.
[0011] Preferably, the frosting liquid for the primary frosting in step (2) is composed of the following raw materials in parts by weight: 28-35 parts of ammonium bifluoride, 5-8 parts of ammonium fluoride, 3-5 parts of sodium fluorosilicate, 6-12 parts of aminosulfonic acid, 1-4 parts of barium sulfate, 1-4 parts of bentonite, 12-19 parts of ferric chloride, 4-8 parts of potassium nitrate, 4-7 parts of potassium fluoride, and 18-28 parts of water.
[0012] Preferably, the frosting liquid for the secondary frosting in step (3) is composed of the following raw materials in parts by weight: 14-20 parts of ammonium bifluoride, 6-10 parts of citric acid, 2-5 parts of barium sulfate, 1-4 parts of hydroxy starch, 5-9 parts of ferric chloride, 11-16 parts of potassium nitrate, 12-17 parts of potassium fluoride, 4-6 parts of sodium sulfate, and 26-35 parts of water.
[0013] Preferably, the temperature of the secondary frosting in step (3) is 40-80s, and the temperature is 18-28°C.
[0014] Preferably, the chemical polishing treatment liquid in step (4) is composed of the following raw materials in percentage by mass: 5%-7% hydrogen fluoride, 1%-5% sulfuric acid, 1%-3% ammonium bifluoride, 0.2-0.6% sodium cellulose, and 84%-94% water; the treatment time of the chemical polishing is 15-30 minutes, and the treatment temperature is 33-42°C.
[0015] Preferably, the acid-resistant ink is removed in step (4) by using alkaline solution.
[0016] Further preferably, the alkali solution removal condition is 40-45° C. and the time is 8-12 min.
[0017] More preferably, the alkali solution is sodium hydroxide with a mass percentage of 10-12%.
[0018] The beneficial effect of the present invention is that the glass is processed by using a two-time frosting + chemical polishing process, and the frosting liquid formula used in each frosting is different. Relatively large grains are formed on the glass surface during the first frosting, and relatively small grains are formed on the glass surface during the second frosting, thereby forming a layer of special structural crystals on the glass surface. The special structural crystal is that small grains are evenly inlaid around large grains, ensuring that the transmitted light and reflected light of the light inside and outside the glass are controlled within a suitable range, the transmitted light in the screen can clearly display the picture, and the reflected light outside forms a certain diffuse reflection, reducing the proportion of reflected light entering the naked eye and reducing the interference of reflected light; finally, a good anti-glare effect, moderate flash point, and clarity that is more suitable for the experience of the human eye in the vehicle environment are obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is the AG glass crystal prepared in Example 1.
[0020] Figure 2 This is the AG glass crystal prepared in Example 2. DETAILED DESCRIPTION
[0021] The technical solution of the present invention is further explained below in conjunction with the accompanying drawings and specific embodiments. It is worth noting that the following embodiments are only preferred embodiments of the present invention and should not be understood as limiting the present invention. The protection scope of the present invention shall be based on the contents recorded in the claims. Any modification or replacement made by those skilled in the art to the technical solution of the present invention without creative work shall fall within the protection scope of the present invention.
[0022] Example 1 (1) Screen-print acid-resistant ink on one surface of the glass and cure it at 50°C; then pickle the other surface of the glass with 0.5% hydrofluoric acid solution to slightly corrode and passivate the glass surface. After passivation, wash away the residual acid with pure water; (2) Prepare frosting liquid: Primary frosting liquid: 29 parts of ammonium bifluoride, 6 parts of ammonium fluoride, 4 parts of sodium fluorosilicate, 10 parts of aminosulfonic acid, 2 parts of barium sulfate, 2 parts of bentonite, 15 parts of ferric chloride, 5 parts of potassium nitrate, 5 parts of potassium fluoride and 22 parts of water; Secondary frosting liquid: 15 parts of ammonium bifluoride, 8 parts of citric acid, 3 parts of barium sulfate, 2 parts of hydroxy starch, 8 parts of ferric chloride, 14 parts of potassium nitrate, 15 parts of potassium fluoride, 5 parts of sodium sulfate, 30 parts of water; (3) placing the glass obtained in step (1) in a primary frosting liquid, heating it to 25° C. and frosting it, taking it out after 60 seconds and cleaning the surface with 2% hydrofluoric acid, and then washing it with pure water to remove residual acid to obtain a primary glass; (4) placing the primary glass in a secondary frosting solution, heating it to 25°C and frosting it, taking it out after 80 seconds and washing it with pure water to remove residual acid to obtain the secondary glass; (5) drying the secondary glass with hot air, and then placing it in a treatment solution at 40°C for 22 minutes to complete chemical polishing, and then washing with pure water to remove residual acid; wherein the treatment solution is composed of the following raw materials in mass percentage: 7% hydrogen fluoride, 4% sulfuric acid, 1% ammonium bifluoride, 0.6% sodium cellulose, and 87.4% water; (6) The glass obtained in step (5) is placed in a sodium hydroxide solution at 42°C for 10 minutes to remove the acid-resistant ink, then washed with pure water to remove the residual alkali, and finally dried with hot air to obtain a LOW DOI AG glass ( Figure 1 ).
[0023] Example 2 (1) Screen-print acid-resistant ink on one surface of the glass and cure it at 50°C; then pickle the other surface of the glass with 1% hydrofluoric acid solution to slightly corrode and passivate the glass surface. After passivation, wash away the residual acid with pure water; (2) Prepare frosting liquid: Primary frosting liquid: 35 parts of ammonium bifluoride, 5 parts of ammonium fluoride, 5 parts of sodium fluorosilicate, 6 parts of aminosulfonic acid, 1 part of barium sulfate, 4 parts of bentonite, 12 parts of ferric chloride, 6 parts of potassium nitrate, 4 parts of potassium fluoride and 22 parts of water; Secondary frosting liquid: 20 parts of ammonium bifluoride, 6 parts of citric acid, 5 parts of barium sulfate, 1 part of hydroxy starch, 5 parts of ferric chloride, 11 parts of potassium nitrate, 12 parts of potassium fluoride, 6 parts of sodium sulfate, 34 parts of water; (3) placing the glass obtained in step (1) in a primary frosting liquid, heating it to 25° C. and frosting it, taking it out after 80 seconds and cleaning the surface with 2% hydrofluoric acid, and then washing it with pure water to remove residual acid to obtain a primary glass; (4) placing the primary glass in a secondary frosting solution, heating it to 25°C and frosting it, taking it out after 100 seconds and washing it with pure water to remove residual acid to obtain the secondary glass; (5) drying the secondary glass with hot air, and then placing it in a treatment solution at 40°C for 18 minutes to complete chemical polishing, and then washing with pure water to remove residual acid; wherein the treatment solution is composed of the following raw materials in mass percentage: 5% hydrogen fluoride, 5% sulfuric acid, 2% ammonium bifluoride, 0.6% sodium cellulose, and 87.4% water; (6) The glass obtained in step (5) is placed in a sodium hydroxide solution at 42°C for 10 minutes to remove the acid-resistant ink, then washed with pure water to remove the residual alkali, and finally dried with hot air to obtain a LOW DOI AG glass ( Figure 2 ).
[0024] Example 3 (1) Screen-print acid-resistant ink on one surface of the glass and cure it at 50°C; then pickle the other surface of the glass with 0.8% hydrofluoric acid solution to slightly corrode and passivate the glass surface. After passivation, wash away the residual acid with pure water; (2) Prepare frosting liquid: Primary frosting liquid: 28 parts of ammonium bifluoride, 8 parts of ammonium fluoride, 3 parts of sodium fluorosilicate, 12 parts of aminosulfonic acid, 4 parts of barium sulfate, 1 part of bentonite, 17 parts of ferric chloride, 4 parts of potassium nitrate, 5 parts of potassium fluoride and 18 parts of water; Secondary frosting liquid: 20 parts of ammonium bifluoride, 6 parts of citric acid, 5 parts of barium sulfate, 1 part of hydroxy starch, 5 parts of ferric chloride, 11 parts of potassium nitrate, 12 parts of potassium fluoride, 6 parts of sodium sulfate, 34 parts of water; (3) placing the glass obtained in step (1) in a primary frosting liquid, heating it to 25° C. and frosting it, taking it out after 80 seconds and cleaning the surface with 2% hydrofluoric acid, and then washing it with pure water to remove residual acid to obtain a primary glass; (4) placing the primary glass in a secondary frosting solution, heating it to 25°C and frosting it, taking it out after 40 seconds and washing it with pure water to remove residual acid to obtain the secondary glass; (5) drying the secondary glass with hot air, and then placing it in a treatment solution at 40°C for 18 minutes to complete chemical polishing, and then washing with pure water to remove residual acid; wherein the treatment solution is composed of the following raw materials in mass percentage: 7% hydrogen fluoride, 5% sulfuric acid, 3% ammonium bifluoride, 0.6% sodium cellulose, and 84.4% water; (6) The glass obtained in step (5) is placed in a sodium hydroxide solution at 42° C. for 10 min to remove the acid-resistant ink, then washed with pure water to remove residual alkali, and finally dried with hot air to obtain low DOI AG glass.
[0025] Example 4 (1) Screen-print acid-resistant ink on one surface of the glass and cure it at 50°C; then pickle the other surface of the glass with 1% hydrofluoric acid solution to slightly corrode and passivate the glass surface. After passivation, wash away the residual acid with pure water; (2) Prepare frosting liquid: Primary frosting liquid: 28 parts of ammonium bifluoride, 6 parts of ammonium fluoride, 3 parts of sodium fluorosilicate, 8 parts of aminosulfonic acid, 2 parts of barium sulfate, 2 parts of bentonite, 12 parts of ferric chloride, 5 parts of potassium nitrate, 6 parts of potassium fluoride and 28 parts of water; Secondary frosting liquid: 14 parts of ammonium bifluoride, 6 parts of citric acid, 2 parts of barium sulfate, 3 parts of hydroxy starch, 6 parts of ferric chloride, 16 parts of potassium nitrate, 16 parts of potassium fluoride, 5 parts of sodium sulfate, 32 parts of water; (3) placing the glass obtained in step (1) in a primary frosting liquid, heating it to 25° C. and frosting it, taking it out after 100 seconds and cleaning the surface with 2% hydrofluoric acid, and then washing it with pure water to remove residual acid to obtain a primary glass; (4) placing the primary glass in a secondary frosting solution, heating it to 25°C and frosting it, taking it out after 60 seconds and washing it with pure water to remove residual acid to obtain the secondary glass; (5) drying the secondary glass with hot air, and then placing it in a treatment solution at 40°C for 25 minutes to complete chemical polishing, and then washing with pure water to remove residual acid; wherein the treatment solution is composed of the following raw materials in mass percentage: 6% hydrogen fluoride, 3% sulfuric acid, 1% ammonium bifluoride, 0.5% sodium cellulose, and 89.5% water; (6) The glass obtained in step (5) is placed in a sodium hydroxide solution at 40° C. for 12 minutes to remove the acid-resistant ink, then washed with pure water to remove residual alkali, and finally dried with hot air to obtain low DOI AG glass.
[0026] Example 5 (1) Screen-print acid-resistant ink on one surface of the glass and cure it at 50°C; then pickle the other surface of the glass with 0.5% hydrofluoric acid solution to slightly corrode and passivate the glass surface. After passivation, wash away the residual acid with pure water; (2) Prepare frosting liquid: Primary frosting liquid: 32 parts of ammonium bifluoride, 5 parts of ammonium fluoride, 3 parts of sodium fluorosilicate, 6 parts of aminosulfonic acid, 1 part of barium sulfate, 1 part of bentonite, 19 parts of ferric chloride, 8 parts of potassium nitrate, 7 parts of potassium fluoride and 18 parts of water; Secondary frosting liquid: 15 parts of ammonium bifluoride, 10 parts of citric acid, 3 parts of barium sulfate, 4 parts of hydroxy starch, 9 parts of ferric chloride, 14 parts of potassium nitrate, 17 parts of potassium fluoride, 4 parts of sodium sulfate, 24 parts of water; (3) placing the glass obtained in step (1) in a primary frosting liquid, heating it to 18° C. and frosting it, taking it out after 120 seconds and cleaning the surface with 1% hydrofluoric acid, and then washing it with pure water to remove residual acid to obtain a primary glass; (4) placing the primary glass in a secondary frosting solution, heating it to 18°C and frosting it, taking it out after 120 seconds and washing it with pure water to remove residual acid to obtain the secondary glass; (5) drying the secondary glass with hot air, and then placing it in a treatment solution and treating it at 33°C for 30 minutes to complete chemical polishing, and then washing it with water to remove residual acid; wherein the treatment solution is composed of the following raw materials in mass percentage: 5% hydrogen fluoride, 1% sulfuric acid, 1% ammonium bifluoride, 0.2% sodium cellulose, and 92.8% water; (6) The glass obtained in step (5) is placed in a sodium hydroxide solution at 40° C. for 15 minutes to remove the acid-resistant ink, then washed with pure water to remove residual alkali, and finally dried with hot air to obtain low DOI AG glass.
[0027] Comparative Example 1 (1) Screen-print acid-resistant ink on one surface of the glass and cure it at 50°C; then pickle the other surface of the glass with 1% hydrofluoric acid solution to slightly corrode and passivate the glass surface. After passivation, wash away the residual acid with pure water; (2) Prepare frosting liquid: 29 parts of ammonium bifluoride, 6 parts of ammonium fluoride, 4 parts of sodium fluorosilicate, 10 parts of aminosulfonic acid, 2 parts of barium sulfate, 2 parts of bentonite, 15 parts of ferric chloride, 5 parts of potassium nitrate, 5 parts of potassium fluoride, and 22 parts of water; (3) placing the glass obtained in step (1) in a frosting liquid, heating it to 25° C. and frosting it, taking out 2% hydrofluoric acid after 60 seconds to clean the surface, and then cleaning it with pure water to remove residual acid to obtain frosted glass; (4) drying the frosted glass with hot air, and then placing it in a treatment solution at 40°C for 22 minutes to complete chemical polishing, and then washing with pure water to remove residual acid; wherein the treatment solution is composed of the following raw materials in mass percentage: 7% hydrogen fluoride, 4% sulfuric acid, 1% ammonium bifluoride, 0.6% sodium cellulose, and 87.4% water; (6) The glass obtained in step (5) is placed in a sodium hydroxide solution at 42° C. for 10 min to remove the acid-resistant ink, then washed with pure water to remove residual alkali, and finally dried with hot air to obtain AG glass.
[0028] Comparative Example 2 (1) Screen-print acid-resistant ink on one surface of the glass and cure it at 50°C; then pickle the other surface of the glass with 1% hydrofluoric acid solution to slightly corrode and passivate the glass surface. After passivation, wash away the residual acid with pure water; (2) Prepare frosting liquid: 15 parts of ammonium bifluoride, 8 parts of citric acid, 3 parts of barium sulfate, 2 parts of hydroxy starch, 8 parts of ferric chloride, 14 parts of potassium nitrate, 15 parts of potassium fluoride, 5 parts of sodium sulfate, and 30 parts of water; (3) placing the glass obtained in step (1) in a frosting liquid, heating it to 25° C. and frosting it, taking it out after 80 seconds and washing it with pure water to remove residual acid to obtain frosted glass; (4) drying the frosted glass with hot air, and then placing it in a treatment solution at 40°C for 22 minutes to complete chemical polishing, and then washing with pure water to remove residual acid; wherein the treatment solution is composed of the following raw materials in mass percentage: 7% hydrogen fluoride, 4% sulfuric acid, 1% ammonium bifluoride, 0.6% sodium cellulose, and 87.4% water; (6) The glass obtained in step (5) is placed in a sodium hydroxide solution at 42° C. for 10 min to remove the acid-resistant ink, then washed with pure water to remove residual alkali, and finally dried with hot air to obtain AG glass.
[0029] Comparative Example 3 (1) Screen-print acid-resistant ink on one surface of the glass and cure it at 50°C; then pickle the other surface of the glass with 0.5% hydrofluoric acid solution to slightly corrode and passivate the glass surface. After passivation, wash away the residual acid with pure water; (2) Prepare frosting liquid: 29 parts of ammonium bifluoride, 6 parts of ammonium fluoride, 4 parts of sodium fluorosilicate, 10 parts of aminosulfonic acid, 2 parts of barium sulfate, 2 parts of bentonite, 15 parts of ferric chloride, 5 parts of potassium nitrate, 5 parts of potassium fluoride, and 22 parts of water; (3) placing the glass obtained in step (1) in a frosting liquid, heating it to 25° C. and frosting it, taking it out after 60 seconds and cleaning the surface with 2% hydrofluoric acid, and then washing it with pure water to remove residual acid to obtain primary glass; (4) placing the primary glass in the frosting liquid again, heating it to 25°C and frosting it, taking it out after 80 seconds and washing it with pure water to remove residual acid to obtain the secondary glass; (5) drying the secondary glass with hot air, and then placing it in a treatment solution at 40°C for 22 minutes to complete chemical polishing, and then washing with water to remove residual acid; wherein the treatment solution is composed of the following raw materials in mass percentage: 7% hydrogen fluoride, 4% sulfuric acid, 1% ammonium bifluoride, 0.6% sodium cellulose, and 87.4% water; (6) The glass obtained in step (5) is placed in a sodium hydroxide solution at 42° C. for 10 min to remove the acid-resistant ink, then washed with pure water to remove residual alkali, and finally dried with hot air to obtain low DOI AG glass.
[0030] Comparative Example 4 (1) Screen-print acid-resistant ink on one surface of the glass and cure it at 50°C; then pickle the other surface of the glass with 0.5% hydrofluoric acid solution to slightly corrode and passivate the glass surface. After passivation, wash away the residual acid with pure water; (2) Prepare frosting liquid: 15 parts of ammonium bifluoride, 8 parts of citric acid, 3 parts of barium sulfate, 2 parts of hydroxy starch, 8 parts of ferric chloride, 14 parts of potassium nitrate, 15 parts of potassium fluoride, 5 parts of sodium sulfate, and 30 parts of water; (3) placing the glass obtained in step (1) in a frosting liquid, heating it to 25° C. and frosting it, taking it out after 60 seconds and cleaning the surface with 2% hydrofluoric acid, and then washing it with pure water to remove residual acid to obtain primary glass; (4) placing the primary glass in the frosting liquid again, heating it to 25°C and frosting it, taking it out after 80 seconds and washing it with pure water to remove residual acid to obtain the secondary glass; (5) drying the secondary glass with hot air, and then placing it in a treatment solution at 40°C for 22 minutes to complete chemical polishing, and then washing with water to remove residual acid; wherein the treatment solution is composed of the following raw materials in mass percentage: 7% hydrogen fluoride, 4% sulfuric acid, 1% ammonium bifluoride, 0.6% sodium cellulose, and 87.4% water; (6) The glass obtained in step (5) is placed in a sodium hydroxide solution at 42° C. for 10 min to remove the acid-resistant ink, then washed with pure water to remove residual alkali, and finally dried with hot air to obtain low DOI AG glass.
[0031] Comparative Example 5 (1) Screen-print acid-resistant ink on one surface of the glass and cure it at 50°C; then pickle the other surface of the glass with 0.5% hydrofluoric acid solution to slightly corrode and passivate the glass surface. After passivation, wash away the residual acid with pure water; (2) Prepare frosting liquid: 22 parts of ammonium bifluoride, 3 parts of ammonium fluoride, 2 parts of sodium fluorosilicate, 5 parts of aminosulfonic acid, 4 parts of citric acid, 2.5 parts of barium sulfate, 1 part of bentonite, 1 part of hydroxy starch, 11.5 parts of ferric chloride, 9.5 parts of potassium nitrate, 10 parts of potassium fluoride, 2.5 parts of sodium sulfate, and 26 parts of water; (3) placing the glass obtained in step (1) in a frosting liquid, heating it to 25° C. and frosting it, taking it out after 60 seconds and cleaning the surface with 2% hydrofluoric acid, and then washing it with pure water to remove residual acid to obtain frosted glass; (4) drying the frosted glass with hot air, and then placing it in a treatment solution at 40°C for 22 minutes to complete chemical polishing, and then washing with water to remove residual acid; wherein the treatment solution is composed of the following raw materials in mass percentage: 7% hydrogen fluoride, 4% sulfuric acid, 1% ammonium bifluoride, 0.6% sodium cellulose, and 87.4% water; (5) The glass obtained in step (4) is placed in a sodium hydroxide solution at 42° C. for 10 min to remove the acid-resistant ink, then washed with pure water to remove residual alkali, and finally dried with hot air to obtain low DOI AG glass.
[0032] Results: The AG glass prepared in the above examples and comparative examples was tested for flash point using a sparkle (SMS-1000), clarity and gloss using a three-angle gloss haze meter (Rhopoint / IQ206085), haze value using a haze meter (PG2000-Pro), and roughness using a roughness meter (Mitutoyo / SJ-210). The results are shown in the following table:
[0033] The results show that by frosting the glass twice and performing chemical polishing once with frosting solutions of different formulations (Examples 1-5), a glass with a flash point of 4 < sparkle < 6, a clarity of 65 < DOI < 80, a haze of 15 < Haza < 25, and a gloss of 20 < G 60 LOW DOI AG glass with comprehensive properties of <40 can be used for vehicle-mounted displays. In Comparative Example 1, the roughness (Ra) of the AG glass prepared by using a primary frosting liquid for a single frosting is relatively large, so it forms a large-grained crystal form. In Comparative Example 2, the roughness (Ra) of the AG glass prepared by using a secondary frosting liquid for a single frosting is relatively small, that is, a fine crystal form is formed. In Comparative Example 3, the AG glass prepared by using a frosting liquid for a double frosting is larger in grains. In Comparative Example 4, the AG glass prepared by using a secondary frosting liquid for a double frosting has larger grains, but the relevant optical parameters do not meet the required indicators. In Comparative Example 5, the optical parameters of the prepared AG glass are not up to standard by mixing the primary and secondary frosting liquids for a single frosting. Therefore, frosting with two frosting liquids alone plus chemical polishing or double frosting cannot obtain AG glass with the required combined optical parameters, and can only make one or two indicators meet the requirements.
[0034] Eye comfort is related to factors such as visual clarity, eye fatigue, glare reaction, and color perception. Visual comfort can be improved by increasing picture clarity, reducing glare reaction, and lighting environment. In addition to the lighting environment, AG glass with combined optical properties can improve eye comfort. However, the clarity and anti-glare reaction of AG glass are not independent, but affect each other. The higher the clarity, the worse the anti-glare; the better the anti-glare, the lower the clarity. Therefore, a suitable combination of optical parameters must be selected to achieve better eye comfort. The clarity of the AG glass prepared in Examples 1-5 is maintained between 68-77, with moderate clarity and good anti-glare effect, which can effectively improve eye comfort.
Claims
1. A method for preparing LOW DOI AG glass, characterized in that: The following steps are involved: (1) Screen print acid-resistant ink on one side of the glass and cure it, and passivate the other side; (2) frosting the glass obtained in step (1), and then washing with acid and water to obtain primary glass; (3) frosting the primary glass for a second time, then washing and air-drying to obtain secondary glass; (4) The secondary glass is chemically polished, and the acid-resistant ink is removed after cleaning and drying, and the low DOI AG glass is obtained by drying.
2. The preparation method according to claim 1, characterized in that: The pickling in step (1) uses a hydrofluoric acid solution with a mass percentage of 0.5-1%.
3. The preparation method according to claim 1, characterized in that: The time of the first frosting in step (2) is 60-120 seconds, and the temperature is 18-28° C.; the pickling adopts a hydrofluoric acid solution with a mass fraction of 1-2%.
4. The preparation method according to claim 1, characterized in that: The frosting liquid for the primary frosting in step (2) is composed of the following raw materials in parts by weight: 28-35 parts of ammonium bifluoride, 5-8 parts of ammonium fluoride, 3-5 parts of sodium fluorosilicate, 6-12 parts of aminosulfonic acid, 1-4 parts of barium sulfate, 1-4 parts of bentonite, 12-19 parts of ferric chloride, 4-8 parts of potassium nitrate, 4-7 parts of potassium fluoride, and 18-28 parts of water.
5. The preparation method according to claim 1, characterized in that: The frosting liquid for the secondary frosting in step (3) is composed of the following raw materials in parts by weight: 14-20 parts of ammonium bifluoride, 6-10 parts of citric acid, 2-5 parts of barium sulfate, 1-4 parts of hydroxy starch, 5-9 parts of ferric chloride, 11-16 parts of potassium nitrate, 12-17 parts of potassium fluoride, 4-6 parts of sodium sulfate, and 26-35 parts of water.
6. The preparation method according to claim 1, characterized in that: The temperature of the secondary frosting in step (3) is 40-80s, and the temperature is 18-28°C.
7. The preparation method according to claim 1, characterized in that: The chemical polishing treatment liquid in step (4) is composed of the following raw materials in percentage by mass: 5%-7% hydrogen fluoride, 1%-5% sulfuric acid, 1%-3% ammonium bifluoride, 0.2-0.6% sodium cellulose, and 84%-94% water; the treatment time of the chemical polishing is 15-30 minutes, and the treatment temperature is 33-42°C.
8. The preparation method according to claim 1, characterized in that: The acid-resistant ink is removed by alkaline solution in step (4).
9. The preparation method according to claim 8, characterized in that: The conditions for removing the alkali solution are 40-45° C. and the time is 8-12 minutes.
10. The preparation method according to claim 9, characterized in that: The mass percentage of the alkali solution is 10-12%.
Citation Information
Patent Citations
Processing technology of low-definition high-transmittance anti-dazzle glass
CN113372009A
Low-flash-point AG glass surface treatment composition and application thereof
CN113880447A
Glass frosting liquid with AG (anti-glare) effect as well as preparation and application of glass frosting liquid
CN114751651A
Multi-texture frosted glass and preparation method thereof
CN114873925A
Frosted glass for rear cover of mobile phone and preparation method of frosted glass
CN118344017A